Analysis of the cutting fluid behavior with a modified micro single-lip deep hole drilling tool. (August 2022) - Oezkaya, Ekrem; Baumann, Andreas; Eberhard, Peter; Biermann, Dirk
Abstract: Deep drilling with smallest diameters is used for applications such as automotive, aerospace and medicine. Especially difficult to cut materials require an efficient tool design to realize an economical production. Therefore, combined simulation methods are used in this paper to analyze the fluid behavior under consideration of the transient chip positions. To improve tool cooling by an improved cutting fluid flow, which supports chip removal also, both the cross-sectional area of the internal cooling channel and the outer and inner cutting edge angles were modified. With the modified model, cutting fluid velocity increased by 40% and chip evacuation by 60%. Graphical Abstract: ga1 Highlights: Cutting fluid analysis by micro deep hole drilling with SPH/DEM and CFD. Efficient fluid flow through modified angle of incidence and cutting edges. Significant increasing of cooling efficiency and process favorable chips. Utilization of the chip attack surfaces and increase of the fluid velocity. Increase the process reliability when machining Inconel 718.